2016
DOI: 10.15361/1984-5529.2016v44n3p421-430
|View full text |Cite
|
Sign up to set email alerts
|

Respostas nutricionais de mudas de sumaúma à adubação nitrogenada, fosfatada e potássica

Abstract: Resumo Objetivou-se no presente estudo avaliar o efeito do nitrogênio (N), do fósforo (P) e do potássio (K) no crescimento de mudas de sumaúma [Ceiba pentandra (L.) Gaertn.]. Para isto, foram conduzidos três experimentos, em casa de vegetação, para avaliar os efeitos desses nutrientes isoladamente, utilizando como substrato Latossolo Amarelo distrófico típico. Foram aplicadas cinco doses de N (50; 100; 125; 150 e 200 kg ha-1 de N), de P (75; 150; 225; 300 e 400 kg ha-1 de P2O5) e de K (40; 80; 120; 160 e 200 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Entretanto, algumas espécies, mesmo que classificadas como pioneiras, não respondem à adubação nitrogenada no início do crescimento. Cardoso et al (2016) não se deve generalizar a resposta ou ausência dela em relação aos grupos ecológicos. A resposta à fertilização nitrogenada depende de inúmeros fatores, como ambiente, genótipo, dose e fonte de nitrogênio (Marques et al 2006).…”
Section: Discussionunclassified
“…Entretanto, algumas espécies, mesmo que classificadas como pioneiras, não respondem à adubação nitrogenada no início do crescimento. Cardoso et al (2016) não se deve generalizar a resposta ou ausência dela em relação aos grupos ecológicos. A resposta à fertilização nitrogenada depende de inúmeros fatores, como ambiente, genótipo, dose e fonte de nitrogênio (Marques et al 2006).…”
Section: Discussionunclassified
“…Other studies report that the addition of K increases biomass production, such as Cruz et al (2011) studying the effect of macronutrients on the production of Peltophorum dubium seedlings. Duarte et al (2015) verified that seedling production of Platymenia foliolosa is stimulated by the association of doses of K and S, obtaining the highest yields using 145 mg dm -³ of K and 45 mg dm -³ of S. Cardoso et al (2016) found that increased N, P and K doses promote the increase of Ceiba pentandra biomass and recommend the use of the 80 kg ha -1 K 2 O dose for seedling production.…”
Section: Introductionmentioning
confidence: 80%
“…The morphological parameters of the seedlings were evaluated in relation to total dry matter (TDM), dry matter of the aerial part (DAM), dry matter of the root (DRM), height (H), diameter of lap (DL), ratio of height/diameter of lap (H/CD) and Dickson quality index (DQI) (Cardoso 2016). The results were submitted to ANOVA (One-Way) and a Tukey test, adjusted to an accuracy of up to 5% probability, using the Agricolae package (Mendiburu, 2020) in the statistical program R 3.6.0 (R Core Team, 2019).…”
Section: Evaluation Of the Effect Of Organic Compost On A Nitens Seementioning
confidence: 99%